Meaningful teaching through research and innovation - Muhammed, Suhaimi (Universiti Teknologi MARA, 2009)
Teaching and research activities are regarded as part and parcel of academia. Teaching and doing research at the same time have become a routine to most of us when we regard these as our preparation to equip ourselves in the learning and teaching process. This paper attempts to highlight the author's personal experience both as a lecturer and researcher. The reward from teaching and research is not merely in the recognition given through awards obtained especially through innovation projects. What is more rewarding is the inner satisfaction when our little effort is acknowledged